If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 18 = -10 Reorder the terms: 18 + 6x = -10 Solving 18 + 6x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 6x = -10 + -18 Combine like terms: 18 + -18 = 0 0 + 6x = -10 + -18 6x = -10 + -18 Combine like terms: -10 + -18 = -28 6x = -28 Divide each side by '6'. x = -4.666666667 Simplifying x = -4.666666667
| 2(-2y+5)-y=-5 | | 3(1.8+-0.4y)-y=8 | | 3y+25=2y+50 | | logy=alogx+b | | 9+-4y=9-4y | | -6x-5y=1 | | 4+3y-3y=4 | | 9n+68=7n+2n-2 | | 0=-4-4x-3x^2 | | 19+(-4y)+4y=19 | | 9x+1=3x-7 | | 9x+1=3x-1 | | 3(4+-2y)+4y=10 | | Y=-4/7x-1/7 | | 15x^2+40x-5=0 | | log(x)=0.40338 | | n^2-12n+21=0 | | e^8-9x=1168 | | 1/3(9)cubed | | 3/x-12/x-3=1 | | X^2+x+121=0 | | 230/360 | | 11/2×e=6 | | (2x+4)(2x+8)(x*x+4)=0 | | x^2-26y+169=0 | | 8x-12-3+3x-21=4.5 | | 4=0.5x+30 | | 30=0.5x+4 | | x(x+2)=7(x+x+2)+71 | | (2x+y)(3x+5y)= | | 15x^2+10=0 | | -4.5q+1.7=-25.8-2q |